2022
DOI: 10.1111/nmo.14506
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence facilitates measuring reflux episodes and postreflux swallow‐induced peristaltic wave index from impedance‐pH studies in patients with reflux disease

Abstract: Background/Aim Reflux episodes and postreflux swallow‐induced peristaltic wave (PSPW) index are useful impedance parameters that can augment the diagnosis of gastroesophageal reflux disease (GERD). However, manual analysis of pH‐impedance tracings is time consuming, resulting in limited use of these novel impedance metrics. This study aims to evaluate whether a supervised learning artificial intelligence (AI) model is useful to identify reflux episodes and PSPW index. Methods Consecutive patients underwent 24‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Research suggests that the application of artificial intelligence models may potentially change this current situation by enabling accurate measurements of reflux episodes and PSPWs. 58 However, further promotion and validation of these models are still required. In the future, we will further optimize the method of data collection and design a prospective study to further verify the conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the application of artificial intelligence models may potentially change this current situation by enabling accurate measurements of reflux episodes and PSPWs. 58 However, further promotion and validation of these models are still required. In the future, we will further optimize the method of data collection and design a prospective study to further verify the conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al recently demonstrated successful use of machine learning methods to identify reflux events in pH/impedance studies ( 10 ). They used ResNet-18, a convolutional neural network commonly used for image recognition, to identify reflux events from pH/impedance studies and reported a sensitivity of 84%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, existing commercial analysis software has not used modern machine learning techniques for development of algorithms or analysis tools to assist with interpretation of these studies. To date, few studies have reported using machine learning methods for interpretation of pH/impedance studies, which include recent studies using a convolutional neural network for study interpretation ( 10 ) or decision tree analysis to identify baseline impedance measurements ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that assessment of PSPW index and MNBI requires additional time for analysis of impedance‐pH tracings 25 : however, given the current limitations of available commercial software for recognition of reflux events, manual analysis of impedance‐pH tracings is regularly warranted 6 and the time required is mainly due to meticulous definition of reflux episodes 11 whereas the additional time needed for calculation of PSPW index and MNBI consists of few minutes only, an extra time justified when the issue is a firm diagnosis of PPI‐refractory GERD, reliable enough to support treatment escalation including surgery. Interestingly, a recent study suggests that artificial intelligence can afford accurate measurement of reflux episodes and PSPWs, thus favoring wider application of impedance‐pH monitoring 26 …”
Section: Discussionmentioning
confidence: 99%